Blanching of papaya: effect on osmotic dehydration and characterization of the fruit invertase - Garcia, Carolina Castilho; Uchidate, Fabio Shindi [UNESP]; Silva, Keila De Souza; Covizzi, Luiz Gustavo; Mauro, Maria Aparecida [UNESP] (Universidade Federal de Santa Maria, 2021)
This research evaluated the influence of blanching on osmotic dehydration in sucrose solutions of papaya of Formosa cultivar. The characterization of invertase present in the fruits was also done. Blanching possibly caused damages to the cellular structure resulting in higher water loss, sugar gain and, thus, effective diffusion coefficients than fresh papayas during osmotic dehydration. The invertase extracted from papaya pulp presented optimum temperature of 45 °C and optimum pH of 4.8. Considering the low production cost of papaya and the invertase characteristics, the fruit shows to be a potential source for the referred enzyme extraction.

O objetivo desse trabalho foi avaliar a influência do branqueamento na desidratação osmótica de mamão Formosa em soluções de sacarose. A caracterização da invertase presente nos frutos também foi realizada. O branqueamento possivelmente danificou a estrutura celular do vegetal resultando em maior perda de água, ganho de açúcar e, consequentemente, maior coeficiente de difusão do que os mamões frescos após a desidratação osmótica. A invertase extraída da polpa do mamão apresentou temperatura ótima de 45 °C e pH ótimo de 4.8. Considerando o baixo custo de produção do mamão e as características da invertase, essa fruta apresenta-se como potencial fonte de extração da enzima.
Branqueamento de mamão: efeito na desidratação osmótica e caracterização da invertase da fruta
Keywords: Carica papaya L.; diffusion coefficient; plant invertase; sugar composition; Carica papaya L.; coeficiente de difusão; invertase vegetal; composição de açúcares.